Change and Promise : Bilingual Deaf Education and Deaf Culture in Latin America - Gerner de García, Barbara; Karnopp, Lodenir Becker (Book collections on Project MUSE., 2016)
Within the past few decades, there has been great progress in deaf education in Latin America and growth in the empowerment of their Deaf communities. However, there is little awareness outside that region of these successes. For the first time, this book provides access, in English, to scholarly research in these areas. Written by Latin American Deaf and hearing contributors, Change and Promise provides a counter argument to external, deficit views of the Latin American Deaf community by sharing research and accounts of success in establishing and expanding bilingual deaf education, Deaf activism, Deaf culture, and wider access for deaf children and adults. Change and Promise describes the historical, cultural, and political contexts for providing bilingual deaf education in Latin America. Bilingual deaf education uses students' sign language, while simultaneously giving them access to and teaching them the majority spoken/written language. This book describes current bilingual deaf education programs in the region that have increased society's understandings of Deaf culture and sign languages. This cause, as well as others, have been championed by successful social movements including the push for official recognition of Libras, the sign language of Brazil. Change and Promise covers this expanding empowerment of Deaf communities as they fight for bilingual deaf education, sign language rights, and deaf civil rights. Despite the vast political and cultural differences throughout Latin America, an epistemological shift has occurred regarding how Deaf people are treated and their stories narrated, from labeling "deaf as handicapped" to being recognized as a linguistic minority. This panoramic study of these challenges and triumphs will provide an invaluable resource for improving outcomes in deaf education and help to secure the rights of deaf children and adults in all societies.